Kinship, neighbourhood and social change in Irish rural communities - Hannan, D (Economic & Social Studies, 1972)
Rural communities in the West of Ireland, even in the most remote, and most traditional areas have experienced immense social organisational and cultural changes during the past twenty years. Indeed, in many respects, these changes appear more fundamental than any occurring in the previous century.
Keywords: Rural Communities; Social Change; Ireland